Konsep Diri dengan Kecemasan pada Narapidana Pengguna Narkotika dalam Menghadapi Masa Depan - Asridayanti - Asridayanti; Sri Aryanti Kristianingsih (Universitas Muhammadiyah Jember, 2021)
This research aimed to analyze the relationship between self-concept and anxiety faced by drug user inmates in facing the future when they are approaching the free period which has undergone 2/3 of the verdict. The subjects in this research were 31 inmates. The sampling technique used was saturated sampling with the criteria of drug user inmates who had undergone 2/3 verdicts at the Narcotics Correctional Institution IIA Yogyakarta. Data were analyzed using product moment correlation from Karl Pearson. The calculation method is assisted by using the SPSS program. The results showed a significant negative relationship between self-concept and anxiety in drug user inmates in facing the future at the Narcotics Correctional Institution IIA Yogyakarta with the correlation coefficient of hypothesis testing obtained at -0.613 with a significance value of 0.000. This means, the more positive the self concept, the lower the level of anxiety in facing the future, and vice versa the more negative the self-concept, the higher the level of anxiety in facing the future.